Pengaruh Kualitas Pelayanan Dan Minat Beli Terhadap Kepuasan Pelanggan Warung Kaki Lima di Batam - Milenia Fitri Setya Putri; Asron Saputra (eCo-Buss, 2023)
The culinary business is a business that is growing rapidly and rapidly, as evidenced by culinary business actors emerging with the latest innovations aimed at attracting customer interest. Likewise with business actors in the Riau archipelago, especially in the city of Batam, the culinary business is experiencing quite good development. It can be seen that there are many culinary delights using concepts that are no less interesting to be the choice of consumers, such as: street food stalls, restaurants, coffee shops, and taverns. So that business actors must improve the quality of service so that consumer buying interest increases as well as customer satisfaction. Service quality is very closely related to customer satisfaction and is an important factor that must be considered by every business actor who aims to attract customers. Likewise with consumer buying interest in addition to good service quality, an ordering system that makes it easier for consumers is also able to attract customer buying interest. So that in this case customer satisfaction is very effective in retaining its customers in a long period of time. The purpose of this study was to determine whether service quality and purchase intention affect customer satisfaction in street food stalls in Batam. Methods of data collection through the distribution of questionnaires with a sample of 383 respondents. The type of research used is quantitative research with multiple regression analysis methods. The results showed that the variable of service quality on customer satisfaction, t value 13.738 > t table 1.966, and Sig 0.000 <0.05, so it can be concluded that the variable service quality has a positive and significant effect on customer satisfaction. The variable of buying interest on customer satisfaction has a t count of 3.245 > t table of 1.966, and a significant 0.001 <0.05 so it can be concluded that the variable of buying interest has a positive and significant effect on customer satisfaction. While simultaneously it can be obtained f count value of 193.790 > f table 3.02 and Sig 0.000 <0.05. Thus it can be concluded that Ho is rejected and Ha is accepted.